ANALISIS SISTEM PELAYANAN ADMINISTRASI DALAM PENERIMAAN PASIEN BPJS DAN PASIEN UMUM RAWAT JALAN RUMAH SAKIT UMUM DAERAH (RSUD) SYEKH YUSUF TAHUN 2023 - Nurul Khairani; Dian Ekawaty; Ricky Perdana Poetra; Sriyani Windarti (Institut Kesehatan Pelamonia, 2025)
Service is a process in direct community needs that are carried out so that people get a satisfaction. Administrative service system is defined as forms of administrative services that are held individually or jointly. This study aims to analyze the administrative service system in accepting BPJS patients and general patients at Syekh Yusuf Hospital, Kab. Gowa. The type of research in this research is descriptive. The sampling technique in this study is using a non-probability sampling techniqu with sample of 228 respondents. The data analysis technique in this study was univariate analysis. Univariate analysis was carried out to obtain an overview or description of each variable. The results showed that the administrative service system in accepting BPJS patients and general patients at Syekh Yusuf Hospital on all indicators namely transparency, accountability, conditional, participatory, equal rights, and the balance of rights and obligations was implemented properly. As for the advice given by the research, it is hoped that tha RSUD Syekh Yusuf will provide clear information, provide effective and efficient services by responding quickly and appropriately, provide opportunities to ask questions about complaints or patient health problems, be fair in providing health services, and provide maximum service to patients.